2019
DOI: 10.1002/jbt.22340
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid as a natural antioxidant compound: Discovery of a potent metabolic enzyme inhibitor for a new therapeutic approach in diabetes and Alzheimer's disease

Abstract: Multiple studies have been recorded on the synthesis and design of multi‐aim anti‐Alzheimer molecules. Using dual butyrylcholinesterase/acetylcholinesterase inhibitor molecules has attracted more interest in the therapy for Alzheimer's disease. In this study, a tannic acid compound showed excellent inhibitory effects against acetylcholine esterase (AChE), α‐glycosidase, α‐amylase, and butyrylcholinesterase (BChE). IC50 values of tannic acid obtained 11.9 nM against α‐glycosidase and 3.3 nM against α‐amylase, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 54 publications
1
23
0
1
Order By: Relevance
“…In the present study, GC (a coumarin) was isolated from G. uralensis and its BChE inhibitory Notably, these IC50 values were much greater than those for AChE inhibition by tannic acid (IC50 = 0.087 µ M) [51], or hesperidin (IC50 = 0.00345 µ M) [52].…”
Section: Discussionmentioning
confidence: 65%
“…In the present study, GC (a coumarin) was isolated from G. uralensis and its BChE inhibitory Notably, these IC50 values were much greater than those for AChE inhibition by tannic acid (IC50 = 0.087 µ M) [51], or hesperidin (IC50 = 0.00345 µ M) [52].…”
Section: Discussionmentioning
confidence: 65%
“…50 and 10.79 µM, respectively) [ 49 ], but less than those of norditerpenoids isograndifoliol and (1 R ,15 R )-1-acetoxycryptotanshinone (IC 50 = 0.9 and 2.4 µM, respectively) [ 50 ]. Notably, these IC 50 values were much greater than those for AChE inhibition by tannic acid (IC 50 = 0.087 µM) [ 51 ], or hesperidin (IC 50 = 0.00345 µM) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out on Korean thistle found that the plant had components which showed α‐glucosidase as well as β‐secretase inhibitory activity which suggested its use as a dietary supplement for treating diabetes and Alzheimer's (Wagle, Seong, Shrestha, Jung, & Choi, ). Recently, a tannic acid compound showed α‐glycosidase inhibitor activity as well as acetylcholine esterase and butyrylcholinesterase inhibitory effect which are useful as a treatment approach in diabetes and Alzheimer's (Türkan, Taslimi, & Saltan, ). Hence, it can be concluded from the literature that there is a growing area of research which explores the potential of antidiabetic drugs in treatment of AD and vice versa.…”
Section: Curing Diabetes Associated Alzheimer's Disease: a Long Way Tmentioning
confidence: 99%